2018
DOI: 10.1177/1744806918783478
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory pain induced GABAergic synaptic plasticity in the adult mouse anterior cingulate cortex

Abstract: BackgroundChronic pain is a persistent unpleasant sensation that produces pathological synaptic plasticity in the central nervous system. Both human imaging study and animal studies consistently demonstrate that the anterior cingulate cortex is a critical cortical area for nociceptive and chronic pain processing. Thus far, the mechanisms of excitatory synaptic transmission and plasticity have been well characterized in the anterior cingulate cortex for various models of chronic pain. By contrast, the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…GABA is the cardinal inhibitory neurotransmitter in the mammalian CNS which involves different functions, such as pain modulation. In fact, GABA exerts its action via ionotropic GABA A and metabotropic BABA B receptors [810,25,3436]. GABA A receptors seem to be the most important and abundant inhibitory receptors in the CNS [11,19].…”
Section: Discussionmentioning
confidence: 99%
“…GABA is the cardinal inhibitory neurotransmitter in the mammalian CNS which involves different functions, such as pain modulation. In fact, GABA exerts its action via ionotropic GABA A and metabotropic BABA B receptors [810,25,3436]. GABA A receptors seem to be the most important and abundant inhibitory receptors in the CNS [11,19].…”
Section: Discussionmentioning
confidence: 99%
“…In complete Freund adjuvant-induced chronic inflammatory pain mice, there are no changes in the protein levels of GABA A subunits, but reduced GAT expression is observed in the ACC. 111 Cancer-induced bone pain (CIBP) is a challenge in patients with advanced cancer. Zhou et al.…”
Section: Effects Of the Gabaergic System In Other Type Of Chronic Painmentioning
confidence: 99%
“…Thibault and his colleagues reported that brain-derived neurotrophic factor expression is increased in the ACC during inflammation and is sufficient to induce a series of plastic changes such as LTP and extracellular regulated protein kinases phosphorylation leading to cold hypersensitivity, and this could be one such mechanism behind the induction and maintenance of the affective-emotional aspect of pain [20]. Koga and his colleagues demonstrated that presynaptic but not postsynaptic changes occur in the β-aminobutyric acid system during early phases in this chronic inflammatory pain model [19].…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have found that there is a close relationship between ACC and inflammatory pain [19]. Thibault and his colleagues reported that brain-derived neurotrophic factor expression is increased in the ACC during inflammation and is sufficient to induce a series of plastic changes such as LTP and extracellular regulated protein kinases phosphorylation leading to cold hypersensitivity, and this could be one such mechanism behind the induction and maintenance of the affective-emotional aspect of pain [20].…”
Section: Discussionmentioning
confidence: 99%